Petrogenesis of the late Cretaceous Budongla Mg-rich monzodiorite pluton in the central Lhasa subterrane, Tibet, China: Whole-rock geochemistry, zircon U-Pb dating, and zircon Lu-Hf isotopes - Liu, Hong; Li, You-Guo; Li, Wen-Chang; Li, Guang-Ming; Ma, Dong-Fang; Ouyang, Yuan; Huang, Han-Xiao; Zhang, Zhi-Lin; Li, Tong; Wu, Jun-Yi (Frontiers in Earth Science, 2022)
Mg-rich monzodiorite are found in the Budongla gold ore district, Zhongba County, Xizang (Tibet) Autonomous Region, P.R. China. Studying the petrogenesis of this intermediate pluton can provide effective information to explore the geological evolution of the Lhasa terrane. One monzodiorite sample yielded a weighted mean 206Pb/238U age of 92.7 ± 1.1 Ma (mean square weighted deviation=0.33) using LA-ICP-MS zircon U-Pb dating, which represents the late phase of Late Cretaceous magmatism. The rock-forming minerals in the Budongla Mg-rich monzodiorite mainly include K-feldspar, plagioclase, quartz, biotite augite, and amphibole, and its accessory minerals mainly include magnetite, titanite, zircon, and apatite. The rocks are rich in K2O+Na2O and K2O with medium contents of SiO2, CaO, and A12O3,, suggesting these rocks belong to the high-K calc-alkaline series. These rocks have high MgO, Fe2O3, and FeO, with high Mg# values and low DI, which implies they are Mg-rich intermediate intrusive rocks. The rocks are enriched in LREEs and LILEs and depleted in HREEs and HFSEs. They have negative Eu anomalies, no obvious negative Ce anomalies, and slightly negative εHf(t). We infer that the Budongla pluton is a high-K calc-alkaline metaluminous Mg-rich monzodiorite and intruded during the post-collisional period of the Lhasa and Qiangtang terranes.